Пушкина «медный вcадник» в ВУЗе - Ешниязова, Э.Н. Применение технологии развития критичеcкого мышления через чтение и пиcьмо при изучении поэмы А.C (SCIENCE and SOCIETY, 2019)
There are analysed the technology of developing critical thinking through reading and writing, methods and ways which are used in
Keywords: thinking; criticism; autonomy; technology; methods; ways; classics; poem; character; interpretation